Rebellion, rascals, and revenue tax follies and wisdom through the ages - Keen, Michael (Princeton University Press, 2021)
An engaging and enlightening account of taxation told through lively, dramatic, and sometimes ludicrous stories drawn from around the world and across the ages. Governments have always struggled to tax in ways that are effective and tolerably fair. Sometimes they fail grotesquely, as when, in 1898, the British ignited a rebellion in Sierra Leone by imposing a tax on huts--and, in repressing it, ended up burning the very huts they intended to tax. Sometimes they succeed astonishingly, as when, in eighteenth-century Britain, a cut in the tax on tea massively increased revenue. In this entertaining book, two leading authorities on taxation, Michael Keen and Joel Slemrod, provide a fascinating and informative tour through these and many other episodes in tax history, both preposterous and dramatic--from the plundering described by Herodotus and an Incan tax payable in lice to the (misremembered) Boston Tea Party and the scandals of the Panama Papers. Along the way, readers meet a colorful cast of tax rascals, and even a few tax heroes. While it is hard to fathom the inspiration behind such taxes as one on ships that tended to make them sink, Keen and Slemrod show that yesterday's tax systems have more in common with ours than we may think. Georgian England's window tax now seems quaint, but was an ingenious way of judging wealth unobtrusively. And Tsar Peter the Great's tax on beards aimed to induce the nobility to shave, much like today's carbon taxes aim to slow global warming. Rebellion, Rascals, and Revenue is a surprising and one-of-a-kind account of how history illuminates the perennial challenges and timeless principles of taxation--and how the past holds clues to solving the tax problems of today.